2020
DOI: 10.1016/j.geb.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of trust: The role of personal experiences

Abstract: Social interactions pervade daily life and thereby create an abundance of social experiences. Such personal experiences likely shape what we believe and who we are. In this paper, we ask if and how personal experiences from social interactions determine individuals' inclination to trust others? We implement an experimental environment that allows us to manipulate prior social experiences-either being paid or not being paid by a peer subject for a task-and afterwards measure participant's willingness to trust o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Social interactions pervade daily life and create an abundance of social experiences. Researchers have found that people’s willingness to trust others is substantially higher after positive social experiences than after negative social experiences [ 14 ]. National health systems and community health systems are complex and consist of layers within which social interactions occur.…”
Section: Resultsmentioning
confidence: 99%
“…Social interactions pervade daily life and create an abundance of social experiences. Researchers have found that people’s willingness to trust others is substantially higher after positive social experiences than after negative social experiences [ 14 ]. National health systems and community health systems are complex and consist of layers within which social interactions occur.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our paper provides some novel insights to the literature on belief formation in prosocial contexts (Fehr et al, 2005) and, in particular, on the determinants of trust (Fehr, 2009;Schwerter and Zimmermann, 2020). To the best of our knowledge, this is one of the very few studies to elicit principals' beliefs of returned effort in a gift-exchange game, and we are one of the first to do so in an incentivized manner.…”
Section: Introductionmentioning
confidence: 85%
“…Individual experiences influence our thoughts, attitudes, and behaviors (Schwerter and Zimmermann 2020). People who did not trust guidelines for public behavior, and acted accordingly, may be more likely to contract the virus (Schwerter and Zimmermann 2020). This could explain the association between infection and lack of trust in authorities' information.…”
Section: Discussionmentioning
confidence: 99%